Context-Dependent Sensitivity to Mutations Disrupting the Structural Integrity of Individual EGF Repeats in the Mouse Notch Ligand DLL1. Issue 3 (20th January 2016) - Schuster-Gossler, Karin; Cordes, Ralf; Müller, Julia; Geffers, Insa; Delany-Heiken, Patricia; Taft, Manuel; Preller, Matthias; Gossler, Achim
Abstract: The highly conserved Notch-signaling pathway mediates cell-to-cell communication and is pivotal for multiple developmental processes and tissue homeostasis in adult organisms. Notch receptors and their ligands are transmembrane proteins with multiple epidermal-growth-factor-like (EGF) repeats in their extracellular domains. In vitro the EGF repeats of mammalian ligands that are essential for Notch activation have been defined. However, in vivo the significance of the structural integrity of each EGF repeat in the ligand ectodomain for ligand function is still unclear. Here, we analyzed the mouse Notch ligand DLL1. We expressed DLL1 proteins with mutations disrupting disulfide bridges in each individual EGF repeat from single-copy transgenes in the HPRT locus of embryonic stem cells. In Notch transactivation assays all mutations impinged on DLL1 function and affected both NOTCH1 and NOTCH2 receptors similarly. An allelic series in mice that carried the same point mutations in endogenous Dll1, generated using a mini-gene strategy, showed that early developmental processes depending on DLL1-mediated NOTCH activation were differently sensitive to mutation of individual EGF repeats in DLL1. Notably, some mutations affected only somite patterning and resulted in vertebral column defects resembling spondylocostal dysostosis. In conclusion, the structural integrity of each individual EGF repeat in the extracellular domain of DLL1 is necessary for full DLL1 activity, and certain mutations in Dll1 might contribute to spondylocostal dysostosis in humans.